A Facile Strategy for Low Young's Modulus PDMS Microbeads Enhanced Flexible Capacitive Pressure Sensors (Part. Part. Syst. Charact. 7/2021). (19th July 2021) - Sun, Yupeng; Tai, Huiling; Yuan, Zhen; Duan, Zaihua; Huang, Qi; Jiang, Yadong
Abstract : In article 2100019, Tai, Yuan, and co‐workers present a facile strategy to fabricate a capacitive pressure sensor with polydimethylsiloxane microbeads decorated dielectric layer, endowing it with superior performance. Based on that, the microbeads decorated sensor is utilized for human motion monitoring.